Basic income or a single tapering rule? Incentives, inclusiveness and affordability compared for the case of Finland - Pareliussen, Jon (OECD Economics Department Working Papers, 2018)
The combination of different working-age benefits, childcare costs and income taxation creates complexity, reduces work incentives and holds back employment. This paper compares Finland's benefit system with two benefit reform scenarios: a uniform benefit for all ("basic income") and a universal tapering rule ("universal credit"). The scenarios are modelled in the OECD TaxBen model and the TUJA microsimulation model. We find that replacing current benefits with a basic income would improve incentives for many, but with a drastic redistribution of income and likely increasing poverty as a result. Merging working-age benefits with similar aims and coordinating their tapering against earnings would on the other hand consistently improve work incentives and transparency, while preserving or improving social protection